Holy Relics and the Image of Early Medieval Dalmatian Cities: Structural Analysis of the Legends of Translations - Vedriš, Trpimir (2005)
The aim of the presentation is to trace and analyse the relation between the identity (or self-perception) of the early medieval urban communities and their alleged connections to the Classical and Christian past as reflected in the accounts of the translations of the relics. The Translationes, a hybrid hagiographic sub-genre connecting the hagiographic Vitae and "more historical" forms such a chronicles, were often disregarded in Croatian historiography as the sources of low historical value. This was primarily due to the inadequate approach to their reading. Although these documents indeed contain a little "historical" data, they are nevertheless a precious source for investigation of medieval religiosity and its relations to the early medieval urban identities. Tracing the basic narrative elements and the structure of the legends, the author aims to detect the conceptual patterns as the expression of the significance of the translations of the relics and their relation to communities' past. The texts to be analysed are the legends of the early medieval translations of the relics of St. Euphemia to Rovinj, St. Anastasia and St. Chrysogonus to Zadar, St. Domnius and St. Anastasius to Split and St. Trypho to Kotor.
Projekt MZOS
ENG